The vascular flora of the lower Sieve Valley (Tuscany, central Italy) - Lorenzo Pinzani (Italian Botanist, 2025)
A comprehensive checklist of vascular flora occurring in the lower Sieve Valley basin (province of Florence, Tuscany) is presented. Despite its economic and agricultural significance, this territory has been largely overlooked by botanists, resulting in a substantial gap in floristic information. The checklist is based on bibliographic analysis and field studies carried out between 2018 and 2024. A total of 1034 spontaneous taxa (species and subspecies), including 141 aliens, are reported for the territory. Of these, 21 taxa represent new records or confirmations for the province of Florence and 893 taxa are new to the lower Sieve Valley. Tilia americana L. and Sequoia sempervirens (D.Don) Endl. are newly reported for Tuscany and Populus × canadensis Moench nothosubsp. canadensis should be considered as a naturalized alien in the region. Life forms and chorotypes exhibit pronounced Eurosiberian affinities, with a significant contribution from Mediterranean plants. This pattern aligns with the temperate and continental climate of the area, which is partially influenced by summer aridity.